Analisis Profitabilitas, Ukuran Perusahaan, Struktur Aset, Likuiditas, dan Risiko Bisnis terhadap Struktur Modal Perusahaan Manufaktur di Indonesia - Velda Lianto; Annisa Nauli Sinaga; Elvi Susanti; Christina Yaputra; Veronica Veronica (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Capital structure reflects the extent to which companies can manage existing capital to generate profits. The purpose of this research is to examine and analyze the influence of variables of profitability, firm size, asset structure, liquidity, and business risk on the capital structure in Manufacturing companies listed on the Indonesia Stock Exchange in the period of 2015 - 2018. The sampling technique uses purposive sampling by determining 3 criteria. From total of 155 companies, only 69 companies were sampled. The result of this research indicate that profitability has a positive and significant effect on capital structure, firm size has a positive and no significant effect on capital structure, asset structure has no effect and no significant on capital structure, liquidity and business risk have a negative and significant effect on capital structure in Manufacturing companies listed on the Indonesia Stock Exchange in the periode of 2015 - 2018. Keywords: Profitability, Firm Size, Asset Structure, Liquidity, Business Risk and Capital Structure